2019
DOI: 10.1007/s11192-019-03156-2
|View full text |Cite
|
Sign up to set email alerts
|

Publication modalities ‘article in press’ and ‘open access’ in relation to journal average citation

Abstract: There has been a generalization in the use of two publication practices by scientific journals during the past decade: 1. 'article in press' or early view, which allows access to the accepted paper before its formal publication in an issue; 2. 'open access', which allows readers to obtain it freely and free of charge. This paper studies the influence of both publication modalities on the average impact of the journal and its evolution over time. It tries to identify the separate effect of access on citation in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
13
0
2
Order By: Relevance
“…Judging from the perspective of quality, in both WoS and Scopus, OA journals are selected for indexing by applying the same criteria and policies as for the rest of indexed sources. Although OA journals indexed in the DBs are usually being estimated as having lower citation impact indicator values for the time being [128,152], this could be at least partially explained by the fact that many of OA journals are relatively new. However, the quality of indexed OA journals has not been compared between WoS and Scopus.…”
Section: Open Access Content and "Predatory" Journalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Judging from the perspective of quality, in both WoS and Scopus, OA journals are selected for indexing by applying the same criteria and policies as for the rest of indexed sources. Although OA journals indexed in the DBs are usually being estimated as having lower citation impact indicator values for the time being [128,152], this could be at least partially explained by the fact that many of OA journals are relatively new. However, the quality of indexed OA journals has not been compared between WoS and Scopus.…”
Section: Open Access Content and "Predatory" Journalsmentioning
confidence: 99%
“…However, the quality of indexed OA journals has not been compared between WoS and Scopus. On the other hand, as there is often highlighted that papers published by OA model and OA journals in general are prone to receive more citations than ones that are published in traditional ways due to the wider and faster accessibility of OA content, the quality of OA journals estimated by citations, and citation-based indicators may very fast reach and even overgrow the values of traditional journals [149,152]. Indeed, many studies have demonstrated that OA content attracts more citations [129,133,[153][154][155], although others did not observe significant OA advantage in citation impact [156,157].…”
Section: Open Access Content and "Predatory" Journalsmentioning
confidence: 99%
“…Although, advanced publication known as "article in press" appears to affect both metrics. The use of citations of advanced publications to determine the impact is still controversial and models have been proposed to handle such scenarios 30 . Retractions and self-citations have also been implicated in changing the dynamics of the metrics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The open access journals and books are available to the broader researcher community to access, browse, consult and further built their work. So, open access documents get more citations, which increase the RCI and CPP value of authors (González-Betancor and Dorta-González, 2019). The RCI value follows similar trends as CPP (Table 9).…”
Section: Core Sources Of Grey Literaturementioning
confidence: 67%